FIVES: A RECENT STRATEGY IN TEACHING READING COMPREHENSION - Eka Melati (Universitas Negeri Padang, 2018)
Reading comprehension strategies define as plans and sets of steps used by efficient readers to understand the text intentionally. Instruction of comprehension strategy helps students becoming efficient readers who select and apply multiple skills suited to a text, their level of background knowledge, and intended purpose as they construct meaning. But before that outcome can be achieved, the students must be taught useful reading skills, allowed enough time for supported practice with each and be provided with models of strategies integration across multiple texts for authentic purposes. With an effective and efficient information and suggestions available for teaching students skills, how to use them strategically for comprehension and word learning becomes essential. FIVES (Fact, Inferences, Vocabulary, Experience, Summary) strategy accomodates these high levels of competence instruction in literacy processes and content-specific knowledge and skills. This paper discusses theoretical background of FIVES strategy and how this strategy might be employed in the classroom.